FRI0183 Assessing adherence of ra patients treated with etanercept using etanercept serum trough concentrations and patient self-report. (15th June 2017) - Vogelzang, E; Hebing, R; Nurmohamed, M; L'Ami, M; Krieckaert, C; Wolbink, G
Abstract : Background: The EULAR recommendations for the management of rheumatoid arthritis (RA) update 2013 contained the following research question: "How good is patient adherence to biological agents and can lack of adherence be related to loss of efficacy?" [1]. Limited studies are published in which adherence of RA patients treated with biological disease-modifying anti rheumatic drugs (bDMARDs) has been assessed. Previous studies regarding adherence of RA patients treated with etanercept did not take into account that patients are instructed to temporarily discontinue bDMARDs therapy during e.g. a serious infection. In addition, etanercept concentrations have never been utilized in determining adherence to etanercept in RA patients. Objectives: The aim of our study was to determine the percentage of non-adherent RA patients treated with etanercept, using etanercept concentrations and patient self-report, and to assess the relationship between adherence and clinical outcome during 52 weeks. Methods: Non-adherence was defined as an etanercept trough concentration <0.1ug/mL at least once and no valid/medical reason to miss an etanercept dose. In this retrospective cohort study patients visited our clinic at baseline and 4, 16, 28, 40 and 52 weeks after initiation of etanercept treatment. At baseline and following visits disease activity score of 28 joints (DAS28) was calculated and blood was drawn to measure etanercept concentrations. During each visit patients were asked if they missed an etanercept dose, at which date and for which reason. Remission was defined as DAS28 <2.6 at least for two consecutive visits. Low disease activity (LDA) was defined as DAS28 <3.2 during a minimal of two consecutive visits. Results: In total 292 patients were included. Mean age was 53 years (SD 12.7), 82% was women and median disease duration was 8 years (IQR 3–16). In total 24 patients had an etanercept concentration <0.1ug/mL. Most patients had a medical reason to miss an etanercept dose, see table 1 . Only ten patients (3.4%) were non-adherent during the follow-up of 52 weeks. Of the adherent patients 82 out of 282 (29%) reached LDA versus 1 out of 10 non-adherent patients. A total of 127 of 282 (45%) adherent patients achieved MDA versus 3 out of 10 non-adherent patients. Conclusions: Most patients had a medical reason to miss an etanercept dose. The percentage of patients who are non-adherent to etanercept therapy is very low (3.4%). References: Smolen JS, Landewe R, Breedveld FC, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis 2014;73:492–509. Disclosure of Interest: E. Vogelzang: None declared, R. Hebing: None declared, M. Nurmohamed Speakers bureau: Abbvie, Bristol-Myers Squibb, Merck Sharp & Dohme, Celgene, Pfizer, Roche, Janssen, UCB and Sanofi, M. l'Ami: None declared, C. Krieckaert Speakers bureau: Pfizer and Abbvie, G. Wolbink Grant/research support from: Pfizer, Speakers bureau: Pfizer, UCB and Abbvie